OnlyFans and the Plebeians: Emancipatory moments in contemporary Indonesia - Nawangsari, Tri; Wiesrecker, Sven (Departemen Sosiologi Universitas Gadjah Mada, 2025)
The online platform OnlyFans has attracted a lot of attention in empirical research in recent years. In this analysis, we use a special approach that connects concepts from political philosophy and empirical research. First, we provide a detailed explanation of Jacques Rancière’s notion of the “distribution of the sensible”. Rancière’s example of the plebeians serves to illustrate how certain groups are excluded from participation. Rancière's philosophical perspective on emancipation in Indonesia is of added value because it links the embodiment of roles, which has already been addressed many times in research, with political moments. Secondly, we examine empirical data to explore how OnlyFans is perceived in Bali. By doing so, we trace how narratives surrounding sexuality, morality, and digital labor intersect with local cultural and social frameworks. These insights allow us to identify emerging tensions that reflect deeper structural issues within the social fabric. Thirdly, we argue that these tensions can be read as disruptions of the current social order — ruptures that may reveal emancipatory potential. We interpret them through the lens of Jacques Derrida’s concept of deconstruction. Our aim is not to reconstruct or stabilize social orders, but to highlight the fractures, inconsistencies, and instabilities that reveal the possibility for change within an existing system.